Switching of the Microglial Activation Phenotype Is a Possible Treatment for Depression Disorder - Zhang, Lijuan; Zhang, Jinqiang; You, Zili (Frontiers in Cellular Neuroscience, 2018)
Major depression disorder (MDD) is a common emotional cognitive disorder, which seriously affects people physical, mental health and quality of life. Due to the clinical and etiological heterogeneity, the molecular mechanism of depression is not very clear, and the effect of traditional drug therapy is not ideal. Postmortem and animal studies have shown that over-activated microglia can inhibit neurogenesis in the hippocampus and induce depression-like behaviors. However, the molecular mechanisms by which microglia regulate nerve regeneration and depression-like behaviors are unclear. As immune cells of the central nervous system, microglia can influence neurogenesis through different subtypes, and then affect depression-like behaviors. Microglia are divided into four main states: Under stress, microglia are induced into M1 type, releasing inflammatory factors and causing neuroinflammatory responses; After inflammation fade away, microglia usually show the alternative activated M2 phenotypes that play a role in neuro-protection. M2 subtypes are divided into M2a, M2b, M2c. These phenotypes have different functions in the CNS. Therefore, this article mainly introduces the relationship between microglia and depression. Moreover, this article elucidates the mechanism by which microglia regulate inflammation and neurogenesis in response to MDD. It provides a reliable basis for the treatment of depression in the future.